Diagnostic challenges in suspected mitochondrial disease: Clinical, metabolic, and genetic findings - Secu, Doina; Blanita, Daniela; Usurelu, Natalia; Sacara, Victoria (Acta Medica, 2026)
Objectives: This study delineates the diagnostic architecture of patients referred with suspected mitochondrial disease through the integrated analysis of clinical, biochemical, instrumental, and genetic data. By comparing patients with mitochondrial involvement, alternative genetic disorders, and unresolved cases, we aim to define phenotypic and molecular patterns associated with diagnostic stratification and characterize the diverse spectrum of genetic and non-genetic conditions that converge phenotypically on mitochondrial disease. Materials and Methods: A total of 240 patients with clinical suspicion of mitochondrial disease were consecutively enrolled and assessed using a modified Nijmegen Mitochondrial Disease Score. All participants underwent comprehensive clinical, metabolic, instrumental, and neuroimaging evaluations, complemented by systematic molecular analyses, starting with common mitochondrial variant screening and progressing to more extensive targeted investigations guided by clinical and biochemical findings. Comparative analyses across the three groups employed nonparametric and categorical statistical tests. Results: Relevant molecular findings were identified in 81 patients (33.7%), encompassing 37 (15.4%) with mitochondrial involvement and 44 (18.3%) with alternative genetic disorders, while 159 individuals (66.3%) remained unresolved. The mitochondrial group exhibited significantly higher rates of neuromuscular, brainstem, ophthalmic, and cardiac involvement, along with developmental regression, whereas seizures were a shared hallmark of both mitochondrial and non-mitochondrial subgroups. Biochemically, elevated serum lactate and plasma alanine were the most discriminative markers for the mitochondrial group, with a significantly higher prevalence of abnormal acylcarnitine profiles and organic aciduria in both the mitochondrial and alternative genetic subgroups. The undiagnosed cohort demonstrated phenotypic convergence with confirmed cases but lacked definitive molecular correlates despite extensive evaluation. Conclusions: These findings underscore the intrinsic complexity and phenotypic heterogeneity of suspected mitochondrial disease, affirming the critical role of integrated clinical, metabolic, instrumental, and molecular assessment while simultaneously highlighting the limitations of current diagnostic paradigms and the imperative for expanded genomic and functional strategies to enhance resolution in unresolved cases.